Application Design Performance Assessment And Determination Of Training Needs In PT Sarimelati Kencana - Muhammad, Irfan Zuhdi; Hariadi, Bambang; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Sarimelati Kencana is a company that working in the area of food and beverages. Problem in PT Sarimelati Kencana is often error occurred in the calculation of the assessment. In addition, human resources experienced difficulty in recapping all assessment. It was because PT Sarimelati Kencana still uses sheets of form in assessing. In process of determining employees’ training needs, still found inappropriate training with what employees’ needed.The solution offered is making application to assess performance and determine training needs that can produce computerized data and to ease the implementation of assessment and the determination of training needs, the assessment results recommendation and recapitulation which is suitable with Software Development Life Cycle (SDLC) stage involves planning system, systems analysis, designing system, and the implementation of the system. The result of research showed that application can help the process of performance assessment, training needs determination, and assessment result recapitulation. Keywords : application, performance assessment, training needs